A case of post-transplant lymphoproliferative disorders that developed ten years after living renal transplantation in the parotid gland region. Issue 5 (September 2018) - Sato, Kotaro; Hayashi, Yasushi; Yamamoto, Noriyuki; Ichimura, Norihisa; Hibi, Hideharu
Abstract: Post-transplant lymphoproliferative disorders (PTLDs) are lesions that proliferate lymphocytes or plasma cells and are caused by immunosuppression after organ transplantation or hepatopoietic stem cell transplantation. According to the 2016 WHO classification, PTLDs are classified into four types: early lesions, polymorphic PTLDs, monomorphic PTLDs, and classical Hodgkin lymphoma-type PTLDs. We report a case of PTLD that first occurred in the oral and maxillofacial area more than ten years after living renal transplantation. A sixty-one-year-old man visited our department in the middle of August 2013 because of right parotid gland swelling. We consulted with an otorhinolaryngologist and prescribed antibiotics to determine whether the swelling was parotitis or a tumor; however, the swelling did not improve. At the end of September 2013, a tumor was found in the right palatine tonsil; consequently, a biopsy was performed. After the biopsy, the lesion was diagnosed as monomorphic PTLD (diffuse large B-cell lymphoma), and the patient was admitted to the hematology and oncology ward. Immunosuppressants were interrupted or reduced. However, the tumor continued to swell, and R-CHOP treatment was started. The therapeutic value was PR, and the patient's general condition was good; therefore, in mid-February, he discharged. However, at the end of April 2014, the patient experienced septic shock due to pneumonia and passed away the next day. As this case shows, it is important for oral and maxillofacial surgeons to consider the possibility of PTLD in the oral and maxillofacial area.